Pengaruh Karakteristik Dewan Pengawas Syariah (DPS) Terhadap Kinerja Keuangan Bank Umum Syariah Yang Terdaftar pada Otoritas Jasa Keuangan (OJK) Indonesia - Lila Afiska; Dian Fitria Handayani; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2021)
This paper investigated the effect of the characteristics of the Sharia Supervisory Board (SSB) on the financial performance of Islamic banks listed in Financial Service Authority of Indonesia (OJK) during the period 2016-2020. SSB characteristics consist of size, number of meeting, educational qualification, and reputation. Using purposive sampling, we obtained samples from 13 Islamic Banks in Indonesia. Data was collected from annual report of selected banks for the year 2016-2020 and has been analyzed using the multiple linear regression. The results show that educational qualification of SSB members have significant positive effect on the financial performance. While size, the meeting and reputation of SSB members had no significant effects on the financial performance. This paper gives a comprehensive literature survey on the effect of the characteristics of the Sharia Supervisory Board (SSB) on the financial performance and robustness checks provides support for the findings.